2020
DOI: 10.3390/su12072776
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Adjustment Model of Cruising Taxicab Fleet Size Combined the Operating and Flied Survey Data

Abstract: Due to the lack of adjustment index systems for taxi fleet sizes in China, this paper used the taxi operating datasets from Ningbo City and established a regression tree model to consider the endogenous indicators that affect taxi fleet sizes. Then, a dynamic adjustment mechanism of taxi fleet sizes was proposed by combining the exogenous and endogenous indicators. The importance of the exogenous and endogenous indicators was sorted using the Delphi method. The threshold value of each indicator was also given.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Investigating path decisions possesses superior appliance value (Yu et al 2019;Tang et al 2020). Also, in the fleet adjust experiment, it appears that dynamic fleet size delivers lower cost and higher utilization, while dynamic fleet size adjustment models such like determining when, where and which taxis should join and exit the operation (Ye et al 2020) are missed in this work. Including such appealing models in the future would be more beneficial.…”
Section: Discussionmentioning
confidence: 85%
“…Investigating path decisions possesses superior appliance value (Yu et al 2019;Tang et al 2020). Also, in the fleet adjust experiment, it appears that dynamic fleet size delivers lower cost and higher utilization, while dynamic fleet size adjustment models such like determining when, where and which taxis should join and exit the operation (Ye et al 2020) are missed in this work. Including such appealing models in the future would be more beneficial.…”
Section: Discussionmentioning
confidence: 85%
“…Ehlers et al [45] also demonstrated a further possibility for evaluating a mixed fleet based on an economic efficiency compared to other fleet compositions via a Fleet Efficiency Factor. Recent works based on regression methods are focusing on fleet sizing summarized under the term Mobility on Demand for shared bikes [46][47][48][49], cars and taxis [50][51][52]. Similarities can be found also for the optimum mix and size of air taxi fleets in the aviation industry [53][54][55][56].…”
Section: Vehicle Fleet Sizing Problemsmentioning
confidence: 99%
“…However, due to the regulation of the scale of taxi service, passenger demand is far from being met and usually exceeds taxi supply at peak periods. At the same time, the large number of empty vehicles and high operating cost of taxis seriously restrict the development of the taxi market [1]. In 2015, online car-hailing began to gain in popularity in China.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the mixed method combining LSTM and an attention mechanism was applied to forecast the short-term demand of online car-hailing. The main contributions of this paper are as follows: (1) The importance of temporal and spatial sequences for online car-hailing demand are revealed, which provides a basis for extraction scheduling and dynamic pricing of online car-hailing. (2) Based on the historical data of large-scale online car-hailing, a short-term demand forecasting model of online car-hailing is developed, namely, LSTM + Attention.…”
Section: Introductionmentioning
confidence: 99%